Biologics targeting IL-17 and IL-23 maintain stability in patients with psoriasis during COVID-19 infection: a case-control study - Huang, Dawei; Yu, Yingyuan; Lu, Jiajing; Tan, Fei; Shi, Yuling (Frontiers in Medicine, 2023)
Background: Psoriasis is a chronic and refractory skin disease. The emergence of biologics provides more options for the treatment of psoriasis, but the COVID-19 pandemic poses challenges for the management of psoriasis.The purpose of this study was to investigate the effect of different biologics on the stabilization of psoriasis during COVID-19 infection in China.Methods: This is a single-center, observational, retrospective, case-control study. Using our database, we conducted a remote dermatologic study by means of questionnaire follow-up or telephone follow-up to collect general information of patients, information related to COVID-19 infection and conditions of psoriasis for comparison and further analysis between groups Results: Our study ultimately included 274 patients for analysis. We found that the patients in this collection had mild symptoms of COVID-19 infection, and only 13 of them needed to go to the hospital for medical treatment. Further studies found that in biologics, relative to tumor necrosis factor-α inhibitors (TNF-αi), interleukin-17 inhibitors (IL-17i) and interleukin-23 inhibitors (IL-23i) are both protective factors in flare-up of psoriasis (IL-17i: OR (95%CI) = 0.412 (0.189-0.901); IL-23i: OR (95%CI) = 0.291 (0.097-0.876). In addition, we also found that the proportion of people with increased psoriasis developing long COVID-19 increased, and we speculated that increased psoriasis may be a potential risk factor for long COVID-19.Our study showed that the use of IL-17i and IL-23i was a protective factor for psoriasis compared with TNF-αi, and could keep the psoriasis stable.